První zkušenosti se stimulačním systémem bránice v České republice - Kříž, J; Jaroščiaková, S; Šedivá, K; Hyšperská, V; Čadová, K; Přikrylová, Z (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2023)
Patients with impaired diaphragm function are dependent on long-term mechanical ventilation. It is associated with numerous health complications as well as significant economic burden. Intramuscular diaphragm stimulation through laparoscopic implantation of pacing electrodes is a safe method which enables restoring breathing using diaphragm in a considerable number of patients. The first implantation of diaphragm pacing system in the Czech Republic was performed in a thirty-four-year-old patient suffering from a high-level cervical spinal cord lesion. After eight years of mechanical ventilation support, just five months from initiation of stimulation, the patient is able to breathe spontaneously for ten hours per day on average, with expected total weaning. Once the insurance companies decide to reimburse the pacing system, a widespread use of the method even in patients with other diagnoses, including children, is expected. Key words: electrical stimulation, diaphragm, spinal cord injury, laparoscopic surgery.
Keywords: Diaphragm; umělé dýchání; Electrodes, Implanted; poranění míchy; bránice; dospělí; implantované elektrody; Humans; Adult; Spinal Cord Injuries; elektrostimulační terapie; Czech Republic; Child; Electric Stimulation Therapy; dítě; lidé; Respiration, Artificial; Česká republika